(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the effect of nine years on seasonality, quality, composition, production and the trade price per liter of milk, on a dairy farm in the north of the state of Rio Grande do Sul. Data on fat, protein, lactose, total solids, defatted dry extract, and somatic cell count (SSC), total bacterial count (TBC), monthly sold milk production, average production per animal and trade price per liter of milk. For statistical analysis, analysis of variance was used considering the effect of the seasons (summer, autumn, winter and spring) and years, however, for Pearson’s correlation, the objective was to observe the correlation between the value of the liter of commercialized milk in relation to the milk centesimal composition, microbiological quality and volume of traded milk. Winter and spring were characterized as the seasons with the highest volume of milk sold, the highest lactose levels, the lowest SSC and TBC levels. In relation to the price of the liter of traded milk, the seasons with the highest prices paid were autumn and winter, followed by summer and spring. In addition, this experiment showed that the main components responsible for formulating the price sold per liter of milk were SSC, protein TBC, lactose and volume sold. Thus, the seasons and the different years interfered in the composition, quality, production and price of a liter of milk.